Lenses on teaching : - Chiarelott, Leigh (Thomson Wadsworth, 2007)
This introduction to field experiences for pre-service teachers, LENSES ON TEACHING, is a combined workbook and text student teachers can use to focus their observations in elementary and secondary classrooms. At the beginning of each chapter, the authors cover a broad spectrum of topics related to teaching. Related activities will sharpen your observation and interviewing skills, encourage self-analysis, and foster continued growth